Los debates sobre la participación de las mujeres en el parlamento brasileño: subrepresentación, la violencia y el acoso - Santos, Polianna Pereira dos (2016)
Women were one of the last social groups to conquer political rights in contemporary democracies. Although there are no more legal obstacles for female political participation (active and passive), women’s presence in Brazilian parliaments is minimal. In the Lower House of Parliament (Câmara dos Deputados), after 2014 Elections –that is, 19 years after gender quota regulations in Brazil– women still occupy less than 10% of the seats. That being the case, in this brief study, we revisit cultural, social and institutional variables which are commonly presented as a justification for female under-representation in Brazil. Subsequently, we address gender violence situations which took place in Brazil’s Lower House of Parliament, as well as how they were dealt with by this organization. Furthermore, in attempt to better understand the relations between gender, representation, violence and harassment in the political field, questionnaires were sent to representatives in the Lower House of Parliament, where the two paradigmatic cases which are object of this study took place. In this attempt, we also interview the Vice-Governor of a Brazilian state, a woman who can provide the perspective of the executive branch on the matter. The analysis of these results –including the percentage of answers– should allow us to raise a connection between gender violence in politics and female under-representation.